Investigation of mechanical behavior and properties prediction modelling of copper-filled filament for 3d printing - Kesavarma, Seluraju (2022)
Fused Deposition Modelling (FDM) technology is among the lowest-cost 3D printing technology for processing thermoplastic and composite materials. FDM has been highly used in additive manufacturing due to its ability to process complex parts with accurate dimensions and lowest cost possible. However, FDM technology has a limited working temperature and is unable to melt substances like metals for printing purposes. Thus, thermoplastics materials such as PLA are used in FDM due to their relatively low melting temperature. However, the drawback of these thermoplastic printed through FDM is the lack of mechanical strength and properties such as thermal and electrical conductivity to print functional parts. These problems have led to the development of new composite filament for FDM technique. In this research, 25 wt.%, 50 wt.%, and 80 wt.% of copper reinforced polylactic acid (PLA) specimens have been printed with different infill patterns (Rectilinear, Grid, Concentric, Octagram-spiral, and Honeycomb) using WANHAO 3D printer with printing speed of 30 mm/s, nozzle diameter of 0.4mm, layer height of 0.3mm and extruder temperature at 210 ℃ with print bed temperature of 60 ℃ to study its mechanical properties. The 3D printer was calibrated prior to beginning of test specimens. The infill patterns were set constant at 50 % infill density for all test specimens. The geometry of test specimens was fabricated according to ASTM standards using a low-cost FDM printer. The printing environment is controlled at 20 ℃ to 25 ℃ and 70% to 80% relative humidity. The mechanical properties include tensile properties, and compression properties were investigated. The results of the mechanical tests were then studied using response surface methodology to identify significant parameters that affect the mechanical behaviour and the optimum set of parameters for desired mechanical properties was then proposed. Mathematical models of the mechanical properties were also introduced using response surface methodology, which can be used to predict desired mechanical properties with varying copper composition and infill pattern. From the tensile test, ultimate tensile strength (UTS), Young’s modulus and yield strength (0.2 % offset) were obtained. The highest ultimate tensile strength (UTS) is achieved by the 25 wt.% Cu composition specimens with Concentric infill pattern recording 25.20 MPa. The highest young’s modulus is achieved by the 80 wt.% Cu composition specimens with Concentric infill pattern recording 329.3 MPa. The highest yield strength (0.2% offset is achieved by the 25 wt.% Cu composition specimens with Concentric infill pattern recording 12.81 MPa. The model created for young’s modulus, UTS, and Yield strength has an error of just 0.76%, 0.42%, and 0.19%, respectively. The highest compressive strength is achieved by the Grid infill pattern with 25.94 MPa for 25 wt.% Cu. The highest compressive modulus is achieved by the Grid infill pattern with 555.3 MPa for 80 wt.% Cu. The model created for compressive strength and compressive modulus has an error of just 0.43% and 2.57%. Hence, the Concentric infill pattern with 80 wt.% Cu can provide maximum tensile strength while Grid infill pattern with 25 wt.% Cu can provide maximum compressive strength.